Peran Pemerintah Desa dalam Pemberdayaan Masyarakat Lokal - Andri Nubu; Muhammad Ihsan Mattalitti (Program Studi Ilmu Pemerintahan, Universitas Muhammadiyah Kendari, 2022)
This article provides an overview of the strategic role of village governments in realizing community welfare by involving them in empowerment programs. The concept of community participation has been understood as the most important part in improving the quality of life and development. This study uses a qualitative approach. Data were collected through observation, interviews and documentation. The results showed that the role of the Lanowulu Village government, Tinanggea District, South Konawe Regency had an impact on community involvement and empowerment in the fields of village government, economy and agriculture. These roles include interpersonal roles, information roles and decision-making roles. Of the three roles, not all of them are running optimally, namely the role of information (informational role) and empowerment in the economy, especially micro-enterprises, where the village government has not paid attention to this business, the main obstacle is because the business is not registered at the village office and has not been running. consistent so that the government has not been able to provide. Researchers suggest that the role that has not been implemented must be fulfilled by the village government.